Blending beliefs: how epistemology and islamic principles shape english teaching in the UAE - Al Jobori, Amina; Abdullah, Mohamad Ridhuan (Nun Gemilang Ent, 2024)
This qualitative study investigates the epistemological beliefs of English teachers in the UAE and their influence on teaching practices, using a Critical Narrative design. The research addresses three primary questions related to the nature of knowledge, knowing, and the integration of Islamic principles with modern educational practices. Narrative Inquiry was employed to analyse three stories from the participants. The findings reveal a significant impact of these beliefs on instructional strategies, highlighting the necessity for culturally informed professional development programs. This study contributes to the understanding of how teachers' beliefs shape their pedagogical approaches within a specific cultural context. The implications underscore that religion plays a significant role in harnessing Islamization elements to be instilled in students through the participants' teaching practices.